Analisis Sentimen Opini Mahasiswa Terhadap Aplikasi Portal Mahasiswa UTY Menggunakan Metode Naïve Bayes Classifier - Agus Ardiyanto; Enny Itje Sela (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
University Technology of Yogyakarta (UTY) has released the UTY Student Portal Application since 2020 which is an improvement in services to support student academic activities. The UTY Student Portal application was developed by Puskom from Yogyakarta Technology University. The UTY Student Portal application is a system designed and built to manage data related to academic information which includes student data, lecturer data, lecture results records, lecture schedules and so on. The presence of this Student Portal Application has given rise to various comments from its users, namely UTY students. Seeing this problem, the researchers conducted research on student opinions regarding the UTY Student Portal Application using the Naïve Bayes Classifier. This research uses the Python programming language. Based on the results of the discussion, it was found that the accuracy level was 93% in the training process and the testing accuracy was around 65.2% with a distribution of training and test data of 70%:30% from 150 opinion text data. This model creation experienced overfitting, because the resulting testing accuracy was much smaller than the training accuracy.